Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Prac 3 Bsol

Download as pdf or txt
Download as pdf or txt
You are on page 1of 3

MIT OpenCourseWare

http://ocw.mit.edu

18.02 Multivariable Calculus


Fall 2007

For information about citing these materials or our Terms of Use, visit: http://ocw.mit.edu/terms.
18.02 Practice Exam 3 B – Solutions

� (1,2)

y = 2x

x=1 1� y 2� 1


� �
1. a)
� (1,1)
b) dxdy + dxdy.
0 y/2 1 y/2



�y = x (the first integral corresponds to the bottom half 0 � y � 1, the second
��

� integral to the top half 1 � y � 2.)

r sin �
2. a) �dA = rdrd� = sin �drd�.
r2
�� � �� 3 � � � ��
M= �dA = sin � drd� = 2 sin �d� = − 2 cos � 0 = 4.
R 0 1 0

� 3
1 1
�� � �
b) x̄ = x�dA = r cos � sin �drd�
M R 4 0 1
The reason why one knows that x̄ = 0 without computation is that the region and the density
are symmetric with respect to the y-axis (�(x, y) = �(−x, y)).

3. a) Nx = −12y = My , hence F is conservative.


b) fx = 3x2 − 6y 2 � f = x3 − 6y 2 x + c(y) � fy = −12xy + c� (y) = −12xy + 4y. So c� (y) = 4y,
thus c(y) = 2y 2 (+ constant). In conclusion

f = x3 − 6xy 2 + 2y 2 (+ constant).

c) The curve C starts at (1, 0) and ends at (1, 1), therefore



F · dr = f (1, 1) − f (1, 0) = (1 − 6 + 2) − 1 = −4.
C

4. a) The parametrization of the circle C is x = cos t, y = sin t, for 0 � t < 2�; then dx =
− sin tdt, dy = cos tdt and
� 2�
W = (5 cos t + 3 sin t)(− sin t)dt + (1 + cos(sin t)) cos tdt.
0

b) Let R be the unit disc inside C;


� �� ��
F · dr = (Nx − My )dA = (0 − 3)dA = −3 area(R) = −3�.
C R R

� ��
C3
5. a) (0, 4) •� •� (1, 4) F · n̂ ds = div F dxdy
C� � R ��
= (y + cos x cos y − cos x cos y)dxdy = ydxdy
C4 C2 R R
� 4� 1 � 4

= ydxdy = ydy = [y 2 /2]40 = 8.

(0, 0) •� •� (1, 0) 0 0 0

C1
b) On C4 , x = 0, so F = − sin y ˆ�, whereas n̂ = −ı̂. Hence F · n̂ = 0. Therefore the flux of F
through C4 equals 0. Thus
� � � �
F · n̂ ds = F · n̂ ds − F · n̂ ds = F · n̂ ds ;
C1 +C2 +C3 C C4 C
and the total flux through C1 + C2 + C3 is equal to the flux through C.
� � � �
� ux uy � � 2 −1 �
6. Let u = 2x − y and v = x + y − 1. The Jacobian �� � = � � = 3.

vx vy � � 1 1 �
1

Hence dudv = 3dxdy and dxdy = dudv, so that


3
��
V = (4 − (2x − y)2 − (x + y − 1)2 ) dxdy
(2x−y)2 +(x+y−1)2 <4
1
��
= (4 − u2 − v 2 ) dudv
3
u2 +v 2 <4
2� 2 2� � �2
1 2 2 1
� � �
2
= (4 − r ) rdrd� = r − r4 d�
0 0 3 0 3 12 0
2�
4 8�

= d� = .
0 3 3

You might also like